Understanding Chinese Exceptionalism: China's Rise, Its Goodness, and Greatness. (August 2014) - Ho, Benjamin
As a branch of Chinese political thought, Chinese exceptionalism has recently been the subject of renewed scholarly analysis. By stressing what is unique about China, claims about Chinese exceptionalism seek to provide a different approach to the challenge of global governance, one not dominated by the liberal traditions of the United States and the West more generally. This article argues that Chinese exceptionalism—as understood by the Chinese themselves—represents a nationalistic discourse that attempts to navigate the political and sociological contours concerning what it now means to be Chinese. By stressing what is "good" and "great" about China, Chinese exceptionalism seeks to provide Chinese policy makers substantial traction and legitimacy in the manner in which they choose to frame China's interactions with the outside world.